(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Popliteal Artery Entrapment Syndrome (PAES) is a rare condition caused by compression of the popliteal artery, which affects young patients and is the main cause of intermittent claudication in this population. Methods: Case report, in which an investigation of the case was carried out with Nuclear Magnetic Resonance, arterial Doppler echocardiography and arteriography. Once the suspicion was confirmed and the condition in question was analyzed, clinical treatment with cilostazol and daily walks was defined as therapeutic. Case report: Woman, 29 years old, without comorbidities, seeks medical attention complaining of severe pain in the calf for 2 years with progressive worsening and limiting to walking 50 meters. Conclusion: Although the “main” treatment is surgical, the clinical alternative should be considered due to age, social context, case complexity and patient’s desire.